Progressão escolar : uma (im)possibilidade de inclusão - Wagner, Loiva Inês (2007)
This study consists of an investigation about the impact of the continuing or partial progression of students, in the grade regime, at a public school in the city of Girua, state of Rio Grande do Sul. The progression is ruled in National Education Policies and Bases Law, number 9394/96, and is regulated by the official position number 740/99 of the state of Rio Grande do Sul s Educational Council. The methodological approaching is qualitative and ethnographical based, and it pursues to identify occurred changing in the teachers pedagogical practices, focusing possibilities in order to build ways for a pedagogical praxis under the implementation of the continuing or partial progression of students; to investigate if the progression promotes the inclusion, analyzing the pedagogical practices developed with the passed students in this modality. With this investigation, can be concluded that there were not changing in the teachers pedagogical practice, rather an adjustment to the reality of the progression, giving extra-class works to the students. The progression does not promote the inclusion, even its theoretical assumed fundaments are according to the inclusive education principles, the inclusion does not take place. The levels of abandonment and study repetition have been improved; the students have advanced in grades but with low levels of learning. It has been evident, in the researched school, the difficulties to accomplish a differentiated work, because remain the same excluding evaluative practices, that enforce the inequity and competition. The power is still centered in the teacher, through archaic pedagogies that do not stimulate the learning and cannot both crate the pleasure of learning and realize the education as a way of liberty